2014
DOI: 10.1111/ijal.12062
|View full text |Cite
|
Sign up to set email alerts
|

Coping with English: students' perceptions of their teachers' linguistic competence in undergraduate science teaching

Abstract: This paper addresses the question of how undergraduate students negotiate linguistic competence of their university lecturers following the switch of the classroom medium of instruction from German to English. Emphasizing the concept of intersubjectivity in classroom communities of practice, this paper aims at revealing interpretative repertoires underlying the students' display of the lecturers' communicative behaviour. Discussing selected scenes from two science lectures with undergraduate students, the pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…Regarding the students' proficiency, they describe different episodes of frustration when trying to communicate content knowledge in English and when interacting with lower proficient students: "I found differences between students who come from bilingual schools and can communicate more easily in English and others like me who don't come from bilingual schools" (Student 210). These results confirm what other studies have reported about inadequate language skills of both lecturers and students to cope with bilingual programmes at tertiary level (Smith, 2004;Studer, 2015;Tatzl, 2011;Yusof, Tayib & Mansor, 2004, among others).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the students' proficiency, they describe different episodes of frustration when trying to communicate content knowledge in English and when interacting with lower proficient students: "I found differences between students who come from bilingual schools and can communicate more easily in English and others like me who don't come from bilingual schools" (Student 210). These results confirm what other studies have reported about inadequate language skills of both lecturers and students to cope with bilingual programmes at tertiary level (Smith, 2004;Studer, 2015;Tatzl, 2011;Yusof, Tayib & Mansor, 2004, among others).…”
Section: Resultssupporting
confidence: 90%
“…This confirms results from other studies (e.g. Studer, 2015) in which students perceive that good classroom dynamics may compensate for the lecturers' low level of proficiency. This strengthens the need for an integrated teacher training model, not only in terms of foreign language competence, but also in appropriate EMI methodologies to be used in higher education contexts (Sánchez-Pérez & Salaberri, 2017).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…There has, therefore, been a dichotomy concept of being professional and not being professional based on the students' perceptions, emphasizing to the utility of teaching methods use in the classroom interactions. This finding corroborates the previous study which suggests that negative perceptions of the students towards their program and classroom experiences are primarily due to failure of the teachers' performance of building up interesting and rewarding learning situation (Studer, 2015). Moreover, instead of possessing creativity, the concept of professional and not professional is also attached to the teachers who provide evaluation or not.…”
Section: Teaching Methods Are About Identity and Being Professionalsupporting
confidence: 90%
“…Through negotiation, students engage in a high‐level learning, such as ‘applying,’ ‘understanding,’ or ‘seeing in a new way’ (Lin and Tsai ). This interactional management of communicative problem is critical when nonnative English‐speaking instructors teach a subject like science, since students’ positive classroom experience depends on their instructors’ communicative and didactic skills, rather than formal language proficiency (Studer ). Likewise, as shown in the study of ITA discourse during college office hours by Chiang (), with less resources of the English language than native English‐speaking TAs, ITAs’ interactional management to detect and repair troubles is crucial for reaching mutual understanding with an American student.…”
Section: Literature Reviewmentioning
confidence: 99%